2020 Census: Engaging Social Work and Human Service Leaders and Managers to Make People Count. Issue 3 (26th May 2020) - Murphy-Nugen, Amy B.; Powell, Kortney C.; Grant, Molly K.
ABSTRACT: The 2020 Census is approaching and facing challenges associated with technological innovations and ongoing concerns involving a citizenship question. Census data are used to determine how approximately $675 billion is allocated to states and localities through over 132 federal programs; provide demographic information on which voting maps are drawn; apportion 435 congressional representatives; and provide accurate data on which many human service and social programs are designed, and grant funding is pursued. Social work and human service leaders and managers should inform themselves of the scope of the census and become engaged to ensure that all people are counted.